Calcifying fibrous pseudotumor in association with hyaline vascular type Castleman′s disease - Azam Muhammad; Husen Yousuf; Pervez Shahid (Wolters Kluwer Medknow Publications, 2009)
Calcifying fibrous pseudotumor is a recently described rare entity. It is considered as sclerosing end stage of inflammatory myofibroblastic tumor. An association with hyaline vascular type Castleman′s disease has also been described. We report a case of a 13-year-old boy who presented with pain in epigastrium. Computed tomography scan of abdomen revealed a circumscribed mass arising from the gastric wall along the greater curvature. Histology revealed a tumor composed of spindle cells present within the dense hyalinized collagenous tissue. Lymphoplasmacytic infiltrate was seen along with lymphoid follicles, dystrophic and ossifying calcification. Tumor cells were focally positive for alpha smooth muscle actin and negative for anaplastic lymphoma kinase protein.